STUDENTS’ PERCEPTION ON THE USE OF HUMOR IN ENGLISH TEACHING PROCESS - Muthi'ah Muthi'ah; Syamsul Arif Galib (Universitas Islam Negeri Alauddin Makassar, 2020)
This study examines the use of humor in the teaching process of the English Education Department as perceived by the students. Three main points are discussed in this study: (1) the kinds of lecturers that the students mostly expect to keep them engaged with English tasks in classroom environment, (2) the students’ perception on the use of humor as learning motivator, and (3) the students’ perception on the Lecturers’ Teaching Characters. The participants of the research were the students of the English Education Department at UIN Alauddin Makassar. This research is descriptive. The data were collected using a survey and depth interviews with the students. The results show that the most preferable lecturers are the ones who can make the class/course interesting. Also, while 96% of the students think that using humor in the classroom is important as a learning motivator, the researchers found that lecturers in the English Education Department rarely use humor in the teaching process.